Studi Eksistensi Komunikasi Antarbudaya dalam Komunitas Seminari Menengah Wacana Bhakti - Sidabutar, Franciscus Dicha; Siahaan, Chontina (Universitas Veteran Bangun Nusantara, 2021)
Community life is living together with other people based on one bond, one calling, and one commitment. This study aims to determine whether community life at the Wacana Bhakti Intermediate Seminary can help seminarians get to know other cultures so that cultural exchanges occur in the community, as well as see if there are inaccurate perceptions among seminarians. The respondents of this study were seminarians (community members) in the Wacana Bhakti Minor Seminary starting from grade 1 to the Upper Preparatory Class (KPA). The research method used in this scientific article uses descriptive quantitative methods. The findings in this study indicate that cultural exchange is already owned by almost the entire population and this is supported by intercultural communication that occurs within the community. This can be seen from as many as 58 seminarians who have understood correctly about intercultural communication. The most studied culture in this community is the culture of the Batak and Javanese tribes. Not only that, the researchers found that there are some people who do not even recognize the culture of their own tribe. Therefore, the community may be able to strengthen the communication that occurs between members from different cultures, either directly or indirectly.